Enhancement of short-wavelength range responsibility for PIN silicon photodetectors using additional fluorescent carbon quantum dots nanoparticles. (1st January 2023) - Huang, Hao-Yun; Chen, Jia-Hao; Nan, Feng; Zhou, Lei
Abstract: We demonstrate a hybrid Si photodetector structure by employing an additional layer of fluorescent carbon quantum dot (CQD) nanoparticles constructed on the surface of a Si positive-intrinsic-negative (PIN) photodetector. The experimental studies reveal that the optimized hybrid device can efficiently enhance short-wavelength range responsibility between 300 nm to 600 nm without inducing any deteriorated photodetection performance beyond the short-wavelength region, and thereby achieve broadband sensitivity across the UV–vis-NIR spectra region. The measured photoresponsivity of the optimized device can achieve ∼0.088 A W −1 (@500 nm), which was ∼25% higher than that of a commercial blank PIN Si photodetector.